Hadith #3669 - Sunan al-Nasa'i - Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; ibn Abbas; Muhammad bin al-Salt bin al-Hajjaj محمد بن الصلت بن الحجاج الأسدي; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
“Sufyan narrated to us from Az-Zuhri, from ‘Ubaidullah bin ‘Abdullah, from Ibn ‘Abbas, that Sa’d said: ‘My mother died and there was an (outstanding) vow that she had to fulfill. I asked the Prophet and he told me to fulfill it on her behalf.'”
Grade:

Hadith #3762 - Sunan al-Nasa'i - Abdullah bin Raja' bin 'Umar عبد الله بن رجاء بن عمر/المثني الغداني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Muhammad bin al-Salt bin al-Hajjaj محمد بن الصلت بن الحجاج الأسدي; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan al-Nasa'i)
“Abu Salamah narrated to us, from Abu Hurairah that the Messenger of Allah said: ‘Whoever is given something as a lifelong gift, it belongs to him.'”
Grade:

Hadith #541 - Jami' al-Tirmidhi - Abu Hurairah; Abu Zara' al-Razi أبو زرعة الرازي; Falayh bin Suliaman فليح بن سليمان; Muhammad bin al-Salt bin al-Hajjaj محمد بن الصلت بن الحجاج الأسدي; Sa'id bin al-Harith bin Abi Sa'id سعيد بن الحارث بن أبي سعيد (Jami' al-Tirmidhi)
“When Allah’s Messenger would go out on the day of Eid by one route, he would return by another.”
Grade:

Hadith #1051 - Jami' al-Tirmidhi - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; ibn Abbas; Muhammad bin al-Salt bin al-Hajjaj محمد بن الصلت بن الحجاج الأسدي; Qabws bin Abi Zbyan قابوس بن أبي ظبيان (Jami' al-Tirmidhi)
from the Prophet, similar (to no. 1050), but it does not contain “From Abu Idris” and this is what is correct.
Grade:

Hadith #3463 - Jami' al-Tirmidhi - Abdullah bin 'Abdur Rahman al-Daarimi عبد الله بن عبد الرحمن الدارمي; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; ibn Abbas; Muhammad bin al-Salt bin al-Hajjaj محمد بن الصلت بن الحجاج الأسدي; Muslim bin Sabih al-Hamdani, Abu al-Daha مسلم بن صبيح أبو الضحى (Jami' al-Tirmidhi)
The Prophet (ﷺ) said: “Whoever says: ‘Glory is to Allah, the Magnificent, and with His Praise (Subḥān Allāhil-Aẓīm, wa biḥamdih)’ a date-palm tree is planted for him in Paradise.”
Grade: